(a)
A^(-1) = matrix( 3, 4; -1, -1)
and
B = matrix(1, 6; 2, -3)
You have the inverse of A and (A^(-1))^(-1) = A
For a 2*2 matrix, M = matrix(a,b;c,d)
M^(-1) = 1/(ad - bc)*matrix(d,-b;-c,a)
We have (A^(-1))^(-1) = A = matrix(-1, -4; 1, 3)
2A = matrix(-2, -8; 2, 6)
3B = matrix(3,18; 6,-9)
2A - 3B = matrix(-2-3,-8-18; 2-6,6--9)
=matrix(-5,-26; -4,15)
(b)
The equations can be represents by the matrix A^-1 (the original matrix given in the question) and a column vector.
(A^-1)*matrix(x; y) = matrix(2;4)
If we premultiply by A then:
A(A^-1)*matrix(x; y) = A * matrix(2;4)
matrix(x; y) = A * matrix(2;4)
So,
matrix(x; y) = matrix(-1, -4; 1, 3) * matrix(2;4)
matrix(x; y) = matrix(-1*2 + -4*4 ; 1*2 + 3*4)
matrix(x; y) = matrix(-18 ; 14)
(c)
A + B = matrix(0, 2; 3, 0)
So the determinant is 0*0 - 2*3 = -6
det(A+B)³ = -216
(A + B)³ = matrix(0, 2; 3, 0)*matrix(0, 2; 3, 0)*matrix(0, 2; 3, 0)
(A + B)³ = matrix(6, 0; 0, 6)*matrix(0, 2; 3, 0)
(A + B)³ = matrix(0, 12; 18, 0)
det((A + B)³ ) = 0 - 12*18 = -216
det((A + B)³ ) = (det(A+B))³
I hope this helps.